2012
DOI: 10.1603/ec10420
|View full text |Cite
|
Sign up to set email alerts
|

Host Plant-Related Parasitism and Host Feeding Activities of Diglyphus isaea (Hymenoptera: Eulophidae) on Liriomyza huidobrensis, Liriomyza sativae, and Liriomyza trifolii (Diptera: Agromyzidae)

Abstract: Host plant species can affect the behavior and attributes of parasitoids, such as host searching, oviposition, and offspring fitness. In this study, parasitism, host feeding, and sex ratios of Diglyphus isaea (Walker) (Hymenoptera: Eulophidae) on Liriomyza huidobrensis (Blanchard), Liriomyza sativae Blanchard, and Liriomyza trifolii (Burgess) (Diptera: Agromyzidae) larvae reared on Phaseolus vulgaris L., Pisum sativum L., Solanum lycopersicum L., and Vicia faba L. were determined. In no-choice tests, L. huidob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 39 publications
0
6
1
Order By: Relevance
“…In this rearing procedure, the female proportion was 41%, which was significantly lower than the maximum values of 70–75% of Ode and Heinz () and Musundire et al. (). Production of D. isaea as a biological control agent is expensive, with a large and complex production system.…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…In this rearing procedure, the female proportion was 41%, which was significantly lower than the maximum values of 70–75% of Ode and Heinz () and Musundire et al. (). Production of D. isaea as a biological control agent is expensive, with a large and complex production system.…”
Section: Discussioncontrasting
confidence: 53%
“…Charnov et al (1981) showed the solitary parasitoid adult size is closely correlated with host size. Although host sizes of L. huidobrensis larvae were not measured in this study, studies by Spencer (1973) and Musundire et al (2012) showed that under uniform conditions, L. huidobrensis larvae are larger than those of L. sativae and L. trifolii, suggesting that this species should receive a higher allocation of female progeny compared with larvae of L. sativae and L. trifolii. Thus the female proportion of the parasitoid D. isaea population would be higher when produced from larger host insect species.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…However, differential parasitism would explain the increased predominance only if L. trifolii were more susceptible to parasitization than L. sativae . Surveys show that L. sativae has a rich and diverse parasitoid community in China [24] and other studies have shown that L. sativae may be less susceptible to some common parasitoids than is L. trifolii [18], [25].…”
Section: Discussionmentioning
confidence: 99%
“…Parasitoid species attacking Liriomyza spp. vary in their host plant preference (Musundire et al 2012), so dominant parasitoid species vary between crops (Johnson & Hara 1987). Inevitably, with a polyphagous pest such as Liriomyza sativae, which has a vast host range primarily in the Fabaceae, Cucurbitaceae and Solanaceae, the composition of the parasitoid assemblage varies with the host.…”
Section: Promoting Parasitoids Within Australian Cropping Regionsmentioning
confidence: 99%